The miraculous life of an early Ottoman Saint :|the hagiography of Emîr Sultan - Yaman, Gülser. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The subject of this thesis is Terceme-i Vesîle-i Metâlib, which was translated from Arabic by Zeyn’el-ʿÂbidîn el-Hâc Kâsım. He wrote Emîr Sultan’s hagiography in Arabic in 1543 (H. 950) and then translated it into Turkish. The manuscript has been recorded in AESRY 1060, İstanbul Millet Library. The aim of this thesis is to offer an accurate transliterated version of Terceme-i Vesîle-i Metâlib. It also aims to find out the relationship between six Emîr Sultan’s hagiographies through a comprehensive comparison. Accordingly, this study consists of six chapters. In the first chapter, a short historical background about the hagiography genre and brief information about Emîr Sultan’s life are given. In the second chapter, after giving information about the life of the author based on old and contemporary sources, a detailed examination of the work in terms of content, language, and style has been made. In the third chapter, the relationship among Emîr Sultan hagiographies is questioned by using comparative examination over five Emîr Sultan’s hagiographies and Terceme-i Vesîle-i Metâlib. In the fifth chapter, Terceme-i Vesîle-i Metâlib is introduced, and the methods of textual analysis and transcription system which are used in the last chapter are also described. The transcribed text of Terceme-i Vesîle-i Metâlib is given in the final chapter. Lastly, a facsimile of the manuscript copy is provided at the end of the text.
Keywords: Muslim saints -- Turkey -- Bursa -- Biography.